Short run dynamics of income disparities and regional cycle synchronization - Hasan Engin Duran (European Regional Science Association (ERSA), 2011)
Since the 1990s, the issue of regional income convergence and its long term tendencies has been thoroughly and heatedly discussed. Much less attention, however, has been devoted to the short-run dynamics of regional convergence. In particular, three important aspects have not yet been adequately addressed. Firstly, it is indeed essential to understand whether regional disparities manifest a tendency to move systematically along the national cycle. Then, if this happens to be the case, it becomes crucial to know whether: i. these movements are pro- or counter-cyclical, ii. the cyclical evolution of the disparities is a consequence of differences in the timing with which the business cycle is felt in regions or it is motivated by the amplitude differences across local cyclical swings. In this paper, we shed light on these issues using data on personal income for the 48 coterminous U.S. states between 1969 and 2008.
Keywords: R11; E32; O18; 330; cyclical income disparities; regional business cycles; synchronization